2, 3‐Dichloro‐5, 6‐dicyano‐para‐benzoquinone (DDQ)/Methanesulfonic Acid (MsOH)‐Mediated Intramolecular Arene‐Alkene Oxidative Coupling. Issue 4 (20th February 2014) - Kim, Ko Hoon; Lim, Cheol Hee; Lim, Jin Woo; Kim, Jae Nyoung
Abstract An efficient intramolecular arene‐alkene oxidative coupling of 1, 4‐diaryl‐1, 3‐butadienes has been developed involving the use of a 2, 3‐dichloro‐5, 6‐dicyano‐para‐benzoquinone (DDQ)/acid catalyst. The reaction involves the generation of a radical cation by abstraction of an electron from the substrate with DDQ, an intramolecular Friedel–Crafts‐type reaction, and the loss of hydrogen radical. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>